2022
DOI: 10.3390/su14031608
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Perceptions and Attitudes to Household Air Pollution Exposure and Capability to Change Cooking Behaviours in Urban Rwanda

Abstract: Household air pollution (HAP) from cooking on biomass fuel presents significant health, environmental and socioeconomic consequences worldwide. However, there is a lack of understanding of the factors influencing cooking behaviours that affect HAP exposure in Rwanda (e.g., cooking location, removing children from the cooking area). Sixteen qualitative in-depth interviews were undertaken with women living in an underprivileged neighbourhood in Kigali, Rwanda. Deductive thematic analysis was carried out using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 39 publications
5
4
0
1
Order By: Relevance
“…They identified eye irritation and respiratory problems like coughing, sneezing and asthma were the major health problems caused by household air pollution exposure. This finding corresponds with previously published research [ 27 , 30 , 31 ]. Evidence also suggests air pollution can cause oxidative stress and inflammation in the smaller airways, leading to the exacerbation of asthma and chronic bronchitis, airway obstruction and decreased gas exchange.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…They identified eye irritation and respiratory problems like coughing, sneezing and asthma were the major health problems caused by household air pollution exposure. This finding corresponds with previously published research [ 27 , 30 , 31 ]. Evidence also suggests air pollution can cause oxidative stress and inflammation in the smaller airways, leading to the exacerbation of asthma and chronic bronchitis, airway obstruction and decreased gas exchange.…”
Section: Discussionsupporting
confidence: 94%
“…The barriers to tackle household air pollution are complex and multifaceted, with financial constraints; spouse negligence, lack of full autonomy by the women and lack of knowledge were some of the major challenges mentioned by the study participants. This was also mentioned in previous research in Nepal, Rwanda and Kenya [ 27 , 30 , 31 , 41 ], and possibly due to the lack of involvement of men in maternal healthcare services. It is known in many developing countries that men are the key decision-makers and chief providers of economic resources for their wives and their role is highly influential in women’s health care activities, especially in indoor health [ 42 ].…”
Section: Discussionsupporting
confidence: 67%
“…Both quantitative and qualitative data in this study indicated that the interviewed pregnant women have a relatively high health risk perception related to exposure to HAP. This is in agreement with other qualitative73–75 and mixed76 77 studies that reported most participating women were familiar with the health effects of HAP from biomass fuel use 78 79. Similarly, a study in Rwanda showed that almost all of the respondents reported being concerned for their and their family’s health associated with HAP 80.…”
Section: Discussionsupporting
confidence: 88%
“…The reported high health risks perception of HAP and perceived benefit of improved stove in this study are promising for the effectiveness of future prevention efforts. The health risk perception of any hazards and perceived benefits of certain intervention are reported as key component of many health behaviour change theories 45 47 75 100. Consequently, any public health interventions aimed at reducing HAP in this setting in particular and in LMICs in general need to consider local culture including perception towards the health risk and benefits of intervention for effective adoption and use of interventional technologies as evidenced in previous studies 50 113…”
Section: Discussionmentioning
confidence: 95%
“…Even after accounting for the environmental advantages of conserving trees, the LPG is ahead of biomass stoves. Woolley et al (2022) reported that in Rwanda, levels of HAP source awareness and understanding of the health impacts of air pollution were low among women, reducing their capability to change their behaviour, along with barriers of cost, housing constraints and safety. Abera et al (2021) reported that lack of air pollution regulations were present in 45% of African nations, except for Cameroon, that implemented the WHO guidelines for NO 2 , ozone (O 3 ), PM 10 and PM 2.5 .…”
Section: Health Effectsmentioning
confidence: 99%